2008
DOI: 10.1248/bpb.31.1827
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activation by Umami Substances via Gustatory and Visceral Signaling Pathways, and Physiological Significance

Abstract: Monosodium L-glutamate (MSG) elicits a unique taste termed umami and is widely used as a flavor enhancer in a variety of cuisines. Recent studies suggest the existence of L-glutamate (GLU) receptors and its transduction molecules in the gut mucosa as well as in the oral cavity. The vagal gastric afferent fibers respond specifically to the luminal stimulation of GLU in the stomach. GLU administration in the stomach also activates several brain areas (insular cortex, basal ganglia, limbic system, and hypothalamu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 31 publications
(32 reference statements)
1
34
0
2
Order By: Relevance
“…Furthermore, these investigators made use of intragastric infusions of complex carbohydrates and proteins (polycose vs casein, respectively), raising the possibility that digestive processes independent from postabsorptive metabolic processes influenced the behavioral choices. More recently, an interesting series of studies by Kondoh, Torii, and colleagues have demonstrated specific postingestive effects produced by L-glutamate versus glucose in flavor nutrient-conditioning paradigms (Kondoh and Torii, 2008). In addition to sugar versus L-amino acid conditioning having occurred during different sessions, this latest study differs from ours with respect to the glucose concentrations used: Kondoh et al (2008) intentionally used molar glucose concentrations that are insufficient to induce conditioning (ϳ60 mM).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore, these investigators made use of intragastric infusions of complex carbohydrates and proteins (polycose vs casein, respectively), raising the possibility that digestive processes independent from postabsorptive metabolic processes influenced the behavioral choices. More recently, an interesting series of studies by Kondoh, Torii, and colleagues have demonstrated specific postingestive effects produced by L-glutamate versus glucose in flavor nutrient-conditioning paradigms (Kondoh and Torii, 2008). In addition to sugar versus L-amino acid conditioning having occurred during different sessions, this latest study differs from ours with respect to the glucose concentrations used: Kondoh et al (2008) intentionally used molar glucose concentrations that are insufficient to induce conditioning (ϳ60 mM).…”
Section: Discussionmentioning
confidence: 82%
“…More recently, an interesting series of studies by Kondoh, Torii, and colleagues have demonstrated specific postingestive effects produced by L-glutamate versus glucose in flavor nutrient-conditioning paradigms (Kondoh and Torii, 2008). In addition to sugar versus L-amino acid conditioning having occurred during different sessions, this latest study differs from ours with respect to the glucose concentrations used: Kondoh et al (2008) intentionally used molar glucose concentrations that are insufficient to induce conditioning (ϳ60 mM). Future studies must directly compare the postingestive effects produced by complex carbohydrates and proteins.…”
Section: Discussionmentioning
confidence: 82%
“…The remaining glutamate units are used for the biosynthesis of amino acids (aspartate, alanine, proline), glutathione or proteins. Therefore, glutamate levels in the blood and brain remain stable for several hours following food intake (2,26,61).…”
Section: Glutamate Transporters and Absorptionmentioning
confidence: 99%
“…Ingestion of MSG solutions (240-600 mM) is clearly reduced after selective abdominal vagotomy (24,26). The strengths of the va go t om y -i nd u ce d re du c ti o ns are as fo l lo w s: subdiaphragmatic total vagotomy (TVX) = gastric vagotomy > celiac vagotomy > hepatic vagotomy = intact controls.…”
Section: Effects Of Vagotomy On Msg Ingestive Behaviormentioning
confidence: 99%
See 1 more Smart Citation